2019
DOI: 10.1080/19382014.2019.1601490
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate is not an effective fuel for pancreatic islets and amplifies insulin secretion independent of calcium release from endoplasmic reticulum

Abstract: The aim of the study was to determine the acute contribution of fuel oxidation in mediating the increase in insulin secretion rate (ISR) in response to fatty acids. Measures of mitochondrial metabolism, as reflected by oxygen consumption rate (OCR) and cytochrome c reduction, calcium signaling, and ISR by rat islets were used to evaluate processes stimulated by acute exposure to palmitic acid (PA). The contribution of mitochondrial oxidation of PA was determined in the presence and absence of a blocker of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…Although Weinhouse first mentioned that fatty acid metabolism to CO 2 was similar in tumors and in normal tissues, his group later showed that fatty acids could not be used for ATP synthesis in highly glycolytic hepatomas despite producing normal CO 2 levels (Bloch-Frankenthal et al, 1965;Weinhouse, 1956). More recent studies have confirmed observations that tumor cells produce little ATP from fatty acids (Ta and Seyfried, 2015;Kuok et al, 2019;Lin et al, 2017). It is important to mention that much of the evidence supporting the view that OxPhos is intact or is not seriously compromised in cancer cells comes from in vitro studies.…”
Section: Is Atp Synthesis From Both Fermentation and Oxphos Necessarymentioning
confidence: 97%
See 1 more Smart Citation
“…Although Weinhouse first mentioned that fatty acid metabolism to CO 2 was similar in tumors and in normal tissues, his group later showed that fatty acids could not be used for ATP synthesis in highly glycolytic hepatomas despite producing normal CO 2 levels (Bloch-Frankenthal et al, 1965;Weinhouse, 1956). More recent studies have confirmed observations that tumor cells produce little ATP from fatty acids (Ta and Seyfried, 2015;Kuok et al, 2019;Lin et al, 2017). It is important to mention that much of the evidence supporting the view that OxPhos is intact or is not seriously compromised in cancer cells comes from in vitro studies.…”
Section: Is Atp Synthesis From Both Fermentation and Oxphos Necessarymentioning
confidence: 97%
“…Rather, fatty acids can indirectly stimulate tumor cell growth through SLP-linked fermentation mechanisms. Palmitate is also known to increase OCR through its effects on ATP hydrolysis, rather than through ATP synthesis (Kuok et al, 2019). It is also interesting that glutamine alone can uncouple oxygen consumption from ATP synthesis through its effects on uncoupling protein 2 (UCP2) (Hurtaud et al, 2007).…”
Section: Fatty Acid and Glutamine Stimulation Of Slp In Cancer Cellsmentioning
confidence: 99%
“…Several pathways have been implicated in the pathogenesis of ER stress. Both hyperlipidemia and inflammatory cytokines induce ER Ca 2+ depletion, which impairs chaperones from the protein folding machinery and causes accumulation of misfolded protein [8,10,[15][16][17][18]. Additionally, alteration in miRNA profile under proinflammatory treatment and upregulation of cholesterol synthesis under hyperlipidemia are also suggested to contribute to ER stress in human and rodent β cells [19][20][21][22][23].…”
Section: Effect Of Environmental Stressors On β Cells 21 Endoplasmimentioning
confidence: 99%
“…“Metabolic inflexibility” of the cell to switch between glucose and fatty acid metabolism is well known [ 75 ], and this is supported by our recent indirect calorimetry data showing a decrease in lipid oxidation accompanied by an increase in glucose oxidation after remission of T2DM [ 27 ]. It was reported recently that palmitic acid is not effective fuel for β-cell in rodents [ 76 , 77 ], and this may partially explain β-cell dysfunction in T2DM. Some observational and lipid infusion studies have reported association between NEFA and β-cell function in humans, whereas others found no such evidence [ 23 , 57 , 78 , 79 , 80 ].…”
Section: Lipotoxicity and β-Cell Dysfunctionmentioning
confidence: 99%